Improving epinephrine autoinjector usability and carriage frequency among patients at risk of anaphylaxis: a quality improvement initiative. Issue 3 (23rd September 2022) - Ziyar, Ahdad; Kwon, Jimmy; Li, Arthur; Naderi, Asal; Jean, Tiffany
Abstract : Although epinephrine autoinjectors (EAIs) are crucial for the management of anaphylaxis, patient carriage frequency of EAI is as low as 57% and usage of EAIs is erroneous 35%–43% of the time. Our objective was to improve patient carrying frequency of EAI and understanding of EAI usage. We implemented a quality improvement initiative using consistent closed-loop education, redesigned clinic workflow, electronic medical record reminder-based interventions, and educational materials to improve patient EAI carriage compliance and understanding of EAI indications and proper technique. The percentage of our patients who carried the EAI at all times increased from 55% to 93% in 6 months. Participants knowledge of EAI indications also improved from 22% to 91%. Patient demonstration scores of the EAI device improved from 21% to 91% as well. Our quality improvement interventions demonstrated a significant improvement>80% in EAI carriage frequency, knowledge of indications, and proper device technique.